Seroprevalence of Toxocara canis infection in Czech Republic - Uhlíková, M; Hübner, J (Central European journal of public health, 1998)
An enzyme-linked immunosorbent assay (ELISA) with Toxocara canis excretion--secretion (TES) antigen was used for determination the seroprevalence of Toxocara canis infection in healthy population of several districts in Czech Republic. It was found that the seropositivity ranged from 5.8% to 36.0% in various districts. Valuation by sex, age, profession of the examined persons and different type of their habitation (urban or rural) was used. It is obvious that the percentage of seropositivity rise in dependence on the age of examined persons. This fact may be attributed to the longlasting serological positivity detected in ELISA reaction. Almost in all districts the positivity was higher in inhabitants with a rural type of habitation in comparison with urban residents. The geographical conditions in various districts play an important role in seropositivity of the population too.
Keywords: Male; Child, Preschool; Seroepidemiologic Studies; séroepidemiologické studie; larva migrans viscerální; Adolescent; Infant; Česká republika; Child; dítě; prevalence; Adult; dospělí; mužské pohlaví; protilátky helmintové; ELISA; mladiství; Czech Republic; předškolní dítě; Enzyme-Linked Immunosorbent Assay; Animals; lidé; ženské pohlaví; Humans; zvířata; kojenec; Prevalence; Antibodies, Helminth; Larva Migrans, Visceral; Female; lidé středního věku; Middle Aged; Toxocara canis